HOUSING FINANCE OF AUSTRALIAN ISLAMIC FINANCIAL SERVICE PROVIDERS (IFSPS): AN EMPIRICAL ANALYSIS FROM SHARÃ” CAHPERSPECTIVES - Faruq Ahmad, Abu Umar; Shahed, A. K. M. (International Journal of Economics, Management and Accounting, 2013)
The purpose of this study is to examine the extent of divergence in the practice of Islamic housing finance from the Shari'ah in the Australian context. It presents a discursive analysis of the extent to which the Australian Islamic Financial Service Providers (IFSPs) differ from the traditional Shari'ah in their current practices of Islamic finance by their use of different mortgage products. The study seeks to argue that the Shari'ah compliance of the IFSPs in housing finance should be strictly maintained, and a separate regulatory and legislative framework be established for Islamic housing finance to facilitate its growth since the underlying principles of Islamic finance differ from those of conventional finance. The approach for the study is restricted to critically examining the extent of divergence of Australian IFSPs from the strict Shari'ah compliance in their current use of different financial products and instruments for housing finance. Therefore, it does not attempt to examine any other Islamic products they use for Islamic finance. Besides, it does not evaluate the economic efficiency and profitability or otherwise, of Islamic finance in Australia. In addition to the direct policy recommendations and suggestions for further research it provides for authorities concerned, the study sheds new light on how the challenges of Shari'ah compliance for IFSPs in Australia are met since theShari'ah contracts they use and advertise appear to be traditional mortgage contracts where the borrower takes the risk and the lender gets a fixed rate of return. JEL Classification: G19, G21, Z12 Key words: Islamic housing finance, Shari'ah, Australia